2016
DOI: 10.1371/journal.pone.0146677
|View full text |Cite|
|
Sign up to set email alerts
|

The Acoustic Properties of Low Intensity Vocalizations Match Hearing Sensitivity in the Webbed-Toed Gecko, Gekko subpalmatus

Abstract: The design of acoustic signals and hearing sensitivity in socially communicating species would normally be expected to closely match in order to minimize signal degradation and attenuation during signal propagation. Nevertheless, other factors such as sensory biases as well as morphological and physiological constraints may affect strict correspondence between signal features and hearing sensitivity. Thus study of the relationships between sender and receiver characteristics in species utilizing acoustic commu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 37 publications
0
12
0
1
Order By: Relevance
“…; Chen et al. ), and specifically to the fundamental frequency (Teichroeb et al. ; Lingle & Riede ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…; Chen et al. ), and specifically to the fundamental frequency (Teichroeb et al. ; Lingle & Riede ).…”
Section: Discussionmentioning
confidence: 99%
“…The final hypothesis is that there is a matching between call characteristics and hearing sensitivities, and populations are tuned to the acoustic characteristics of their own distress calls (Manley et al 2014;Chen et al 2016), and specifically to the fundamental frequency (Teichroeb et al 2013;Lingle & Riede 2014). Teichroeb et al (2013) found a positive relation between the mean and the range of fundamental frequencies of mammalian distress calls.…”
Section: Discussionmentioning
confidence: 99%
“…The temperature of the chamber was maintained at 23 ± 1°C. The stimulus presentations, ABR acquisition, equipment control, and data management have been described previously [28, 31]. For each subject three 27 gauge stainless steel electrodes (Rochester Electro-Medical, Inc. FL, USA) were inserted subdermally, at the midline above the medulla (about 3 cm caudal to the snout), above the tympanum and in the ipsilateral front leg as inverting, noninverting and ground electrodes, respectively.…”
Section: Methodsmentioning
confidence: 99%
“…ABR thresholds and latencies were determined using methods described in previous studies [28, 31]. Threshold measurements were defined as the lowest stimulus level for which no responses could be recognized by two experienced observers independently by visual inspection.…”
Section: Methodsmentioning
confidence: 99%
“…Inter-individual interactions have led to the development of complex and dynamic communication systems, including the interaction of different sensory modalities in a multimodal communication model (Partan and Marler, 2005;Bro-Jørgensen, 2010). Lizards, in particular, tend to rely principally on chemical (Mason and Parker, 2010) and visual communication (Ord, Blumstein and Evans, 2002), although acoustic communication may also be present (Chen et al, 2016;Labra, Reyes-Olivares and Weymann, 2016). The interaction between chemical and visual modalities was studied in Sceloporus virgatus (males without ventral colour patches) and Urosaurus ornatus (males possessing ventral colourful patches) lizards (Hews and Benard, 2001), and results show that both species have developed different evolutionary strategies for communication, as each species relies differently upon the chemical or visual modality.…”
Section: Introductionmentioning
confidence: 99%